2017
DOI: 10.1101/119339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytosolic ribosomes on the surface of mitochondria

Abstract: 24By electron cryo-tomography and subtomogram averaging, translation-arrested 25 ribosomes were used to depict the clustered organisation of the TOM complex on the 26 surface of mitochondria, corroborating earlier reports of localized translation. 27Ribosomes were shown to interact specifically with the TOM complex and nascent 28 chain binding was crucial for ribosome recruitment and stabilization. Ribosomes were 29 bound to the membrane in discrete clusters, often in the vicinity of the crista junctions. 30Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…Thus, based on these results, we concluded that mitochondrial targeting occurs co‐translationally, as occurs for SRP‐mediated ER targeting. Indeed, ribosomes are known to be associated with mitochondria (Williams et al, 2014; Gold et al, 2017a, 2017b), which supports our proposed co‐translational targeting to mitochondria. By contrast, there was no competition between the ER and chloroplasts; ER targeting overrode chloroplast targeting at all distances tested between the two TMDs.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, based on these results, we concluded that mitochondrial targeting occurs co‐translationally, as occurs for SRP‐mediated ER targeting. Indeed, ribosomes are known to be associated with mitochondria (Williams et al, 2014; Gold et al, 2017a, 2017b), which supports our proposed co‐translational targeting to mitochondria. By contrast, there was no competition between the ER and chloroplasts; ER targeting overrode chloroplast targeting at all distances tested between the two TMDs.…”
Section: Discussionsupporting
confidence: 87%
“…To investigate which nuclear-encoded mitochondrial transcripts are likely to be located on the surface of mitochondria and hence participate in localized translation (Figure 1A), we established a new protocol for biochemical fractionation (Figure 1B) in zebrafish larvae. Although this approach largely adopts a strategy that was employed to obtain intact mitochondria with associated ribosomes in yeast 17 , it was optimized to obtain a membrane-bound fraction containing mitochondria and ER together with their associated ribosomes. Preservation of ER in this fraction allows us to perform more global analysis of membrane associated nuclear-encoded mitochondrial transcripts, as ER and mitochondria are highly interconnected in the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, the localized translation that occurs at the surface of mitochondria may be directly coupled with the translocation of proteins into organelle. (B) Biochemical fractionation of 5dpf zebrafish larvae based on strategy to obtain intact mitochondria with associated ribosomes in yeast 17 . Isolation of mitochondria with associated ribosomes was performed using a ribosome-friendly buffer (IB-M) containing MgCl 2 , cycloheximide (CHX) and RNAse inhibitors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation